Establishment of Tissue Culture System of Actinidia deliciosa Cultivar “Guichang” - Weimin Zhong; Junliang Zhou; Dongmei Tang; Yaxin Huang; Futao Liu; Min Zhang; Guoli Wang; Sufang Wu; Yue He; Jingwen Tang (Journal of Chemistry)
In order to breed virus-free plantlets of the kiwifruit cultivar “Guichang,” which belongs to Actinidia deliciosa, in this study, stem segments with buds were used as explants, the establishment of a tissue culture rapid propagation system was carried out, and then the virus status of tissue culture plantlets was detected via the real-time reverse transcription-polymerase chain reaction (RT-qPCR) method. The tissue culture rapid propagation system proved that the contamination and browning rates could be controlled below 20% and the survival rate could be exceeded by 70% when the single bud stem segment of “Guichang” kiwifruit was sterilized with 70% alcohol for 30–60 s and 15% NaClO for 15 min, respectively. Meanwhile, we screened the hormone concentration to get better results, and the appropriate medium for adventitious bud induction was MS + 6-BA (1.0 mg/L) + IBA (0.2 mg/L); for proliferation, it was MS + 6-BA (1.0 mg/L) + IBA (0.1 mg/L); and for rooting, it was 1/2 MS + IBA (0.3 mg/L), and the efficiency of induction, proliferation, and rooting could reach 74.07%, 79.63%, and 85.18%, respectively. In addition, the RT-qPCR results demonstrated that the infection rate of 9 viruses: apple stem grooving virus (ASGV), cucumber mosaic virus (CMV), Actinidia virus X (AVX), cucumber necrosis virus (CNV), ribgrass mosaic virus (RMV), citrus leaf blotch virus (CLBV), Actinidia virus B (AcVB), Pelargonium zonate spot virus (PZSV), and cherry leaf roll virus (CLRV) in the “Guichang” kiwifruit tissue culture plantlets was 0. This study could lay a foundation for the production of “Guichang” kiwifruit tissue culture seedlings, and the medium formula provided in this study was useful for the industrial rapid propagation of “Guichang” plantlets.